The influence of loyalty, education &training, and performance on job promotions - Mohamad, Jupri; Abdul Malek, A. Tambi; Mustafa, Mamat; Sukono, .; Ruly, Budiono; Abdul Talib, Bon (2019)
This paper aims: (1) to find out and analyze the influence of loyalty, education & training, and performance, on job promotions; (2) to find out and analyze the effect of loyalty on job promotions; (3) to find out and analyze the effect of education & training on job promotions; and (4) to find out and analyze the effect of performance on job promotions.The study was conducted at the Office of PT. Pos Indonesia (Persero) Tbk. Regional V Bandung. This descriptive causal research was conducted to investigate the relationship between variables involving 80 respondents who had been determined using a sampling method. The data analysis method used is multiple linear regression models.The results of multiple linear regression analysis showed that: (1) loyalty, education & training, and performance simultaneously had a significant effect on job promotions; (2) loyalty performance has a significant effect on job promotions; (3) education & training have a significant effect on the job promotions; and (4) performance has a significant effect on job promotions.